Research on the factors influencing the re-purchase intention on short video platforms: A case of China - Baodeng Lin; Yongyi Chen; Liping Zhang (PLoS ONE, 2022)
Short video platforms, which thrive along with the video-based consumption industry, have become a new channel adopted by an increasing number of enterprises to distribute products. Therefore, it is necessary to study the factors influencing the consumer’s intention to re-purchase on short video platforms, which is helpful for firms to maintain their competitiveness. This paper, based on the customer value theory, seeks to establish a structural model for such factors. The intermediary effect of customer loyalty on customer satisfaction and repurchase intention of customers is also analyzed. Questionnaires were distributed and collected from users of short video platforms in China. Results show that short video content, customer experience, and perceived value have positive impacts on customer satisfaction, and customer satisfaction, along with customer loyalty, exert positive impacts on repurchase intention. Notably, customer loyalty plays an intermediary role between customer satisfaction and repurchase intention. Based on the aforesaid findings, theoretical implications are discussed and managerial implications to increase repurchase rate are offered.